Internationalization of Universities: The German Way - Wahlers, Marijke (International Higher Education, 2018)
While German universities have traditionally followed a partnership-based cooperative approach to internationalization, more recently, growing competition and increasing resource shortages have resulted in the emergence of a more competitive approach. Also with regard to international students as a target group, the cooperative and competitive approaches have coexisted for many years, albeit virtually unconnected. This has resulted in a dramatic increase in the number of international students in Germany over the past two decades. The question arises as to whether, and how, the two sometimes contradictory rationales can, in the future, be harmonized. There is much to be said for Germany further enhancing its international profile in the global competitive market by consistently pursuing its partnership-based approach. There is evidence that not only universities, but also the economy and society, reap long-term benefits.